Destructive Leadership and Counterproductive Work Behavior with Mediation Mechanism of Justice Perception: Evidence from Tanner Sector of Pakistan - Younus, Sohail; Danish, Rizwan Qaiser; Rathore, Kashif (International Review of Management and Marketing, 2020)
The purpose of this study is to examine the relationship among the destructive leadership constructs and counterproductive work behavior (CWB) in tanners sector of Pakistan. Destructive leadership has composed of further two constructs that are Machiavellianism and abusive supervision. The study also investigated the mediating role of justice perception in these relationships. Data was collected from 353 respondents by using self-administered questionnaires from tanners sector of Pakistan. Data were analyzed through Structure equation modeling and test the hypothesized relationships. Results showed the existence of destructive leadership lead to CWB in tanners sector. Justice perception mediates the relationship among destructive leadership and CWB except the relationship of Machiavellianism with Information silence and CWB. Tanneries should conduct different training sessions to reduce the effect of destructive leadership behavior in workplace to reduce the counterproductive work behavior. Future studies may conduct on destructive leadership with horizontal violence and organizational politics. Keywords: Destructive Leadership, Counterproductive Work Behavior, Justice Perception, Tanners Sector, Pakistan JEL Classifications: L20, M12, M54 DOI: https://doi.org/10.32479/irmm.9948